KONSEP BLOCKCHAIN PYTHON DENGAN PENGGUNAAN FLASK HASHLIB - Dwi Kartinah (Asosiasi Dosen Muda Indonesia, 2024)
This research focuses on the development and implementation of a blockchain-based transaction system using the waterfall software development method. This research begins with an analysis of literature regarding blockchain technology and hashing systems to gain an in-depth understanding of the concept and application. At the design stage, the genesis block (first block) was created using the hashlib library in Python, then continued with creating an API using the Flask framework. System implementation is carried out by integrating data transaction and user management functions through a designed API. System testing is carried out to evaluate the functionality and effectiveness of the web-based system that has been implemented. The test results show that the system developed is able to carry out transactions safely and efficiently. Evaluation and improvements are carried out based on test results to ensure the system functions according to user needs.